2014
DOI: 10.3892/mmr.2014.1953
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Myo6 gene expression by co-expression of a mutant of transcription factor POU4F3 (BRN-3C) in hair cells

Abstract: Abstract. An eight-base pair (bp) deletion in the Pou4f3 gene in hair cells is associated with DFNA15, a hereditary form of hearing loss. To explore the pathological mechanisms underlying the development of DFNA15, the effect of the mutation in Pou4f3 on the activity of the myosin VI (Myo6) promoter, was investigated. The upstream regulatory sequence of Myo6 (2625 bp), consisting of an 1899 bp upstream sequence and a 727 bp intron 1 sequence, was amplified using polymerase chain reaction and subcloned into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The diverse histopathologies in hair cell stereocilia, mitochondria and OHC survival of the Pou4f3(Δ/+) mice indicate that the Pou4f3 mutation may affect its transcriptional regulation of genes involved in multiple pathways. We first addressed whether Pou4f3 mutation may affect the expression of known downstream targets, including Lhx3 [8], Gfi1 [7], Bdnf [6], Ntf3 [6], Myo6 [16], Caprin1 [17] and Nr2f2 [18]. We collected cochlear samples from both wildtype and Pou4f3(Δ/+) mutant mice at age of 2 months, when the mutant mice displayed mild hearing loss without significant hair cell loss that may confound gene expression analyses.…”
Section: Plos Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diverse histopathologies in hair cell stereocilia, mitochondria and OHC survival of the Pou4f3(Δ/+) mice indicate that the Pou4f3 mutation may affect its transcriptional regulation of genes involved in multiple pathways. We first addressed whether Pou4f3 mutation may affect the expression of known downstream targets, including Lhx3 [8], Gfi1 [7], Bdnf [6], Ntf3 [6], Myo6 [16], Caprin1 [17] and Nr2f2 [18]. We collected cochlear samples from both wildtype and Pou4f3(Δ/+) mutant mice at age of 2 months, when the mutant mice displayed mild hearing loss without significant hair cell loss that may confound gene expression analyses.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…This family is characterized by the presence of a biparitite DNA binding domain known as the POU domain which comprises a POU-homeo domain and a POU-specific domain separated by a linker, both of which are required for sequence-specific DNA binding [44]. A number of Pou4f3 target genes have been previously identified, including Lhx3 [8], Gfi1 [7], Bdnf [6], Ntf3 [6], Myo6 [16], Caprin1 [17] and Nr2f2 [18]; however, none of these genes showed apparent alterations in the Pou4f3(Δ/+) cochleae examined by RNA-seq or RT-qPCR. One possibility is that changes in expression of these known targets may be subtle and require enrichment of hair cells for their sensitive detection.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Thus, regulation of Atoh1 will affect the expression of Gfi1, and both Atoh1 and POU4F3 are required for maintenance of Gfi1 expression [50]. Another possible mechanism is that the variant of POU4F3 inhibits the expression of myosin VI, which plays a large role in the maintenance of stereocilia of hair cells that are responsible for auditory transduction [51]. Tornari et al reported that the orphan thyroid nuclear receptor Nr2f2, which is related to the development and survival of hair cells, is a target of POU4F3 [52].…”
mentioning
confidence: 99%